2021
DOI: 10.1111/jir.12808
|View full text |Cite
|
Sign up to set email alerts
|

Failure to replicate a robust Down syndrome advantage for maternal well‐being

Abstract: Background Family members caring for children with intellectual disability (ID) routinely report heightened levels of psychological distress. However, families of children with Down syndrome typically report better outcomes (known as the Down syndrome advantage). We examined whether the Down syndrome advantage would be present for maternal psychological distress, impact of caregiving, life satisfaction and perceived positive impact of the child with ID when controlling for external variables. Methods Mothers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Lee et al, 2020; Pruktarat et al, 2021), the measures were positioned as predictors of individual- or family-level adaptation. Seven studies (AlJameel & AlKawari, 2021; Caples et al, 2018; Carrada et al, 2019; Darla & Bhat, 2021; Jess et al, 2021; Ljubicic et al, 2020; Pruktarat et al, 2021) used the measures to assess the impact of other variables on adaptation. The study by J.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lee et al, 2020; Pruktarat et al, 2021), the measures were positioned as predictors of individual- or family-level adaptation. Seven studies (AlJameel & AlKawari, 2021; Caples et al, 2018; Carrada et al, 2019; Darla & Bhat, 2021; Jess et al, 2021; Ljubicic et al, 2020; Pruktarat et al, 2021) used the measures to assess the impact of other variables on adaptation. The study by J.…”
Section: Resultsmentioning
confidence: 99%
“…x Jess et al, 2021 The aim of the current study was to determine whether the DS advantage would be present in both personal (psychological distress and life satisfaction) and child-related (impact of caregiving and positive gains) maternal outcomes when multiple child and maternal variables (e.g., child age, child behavioral and emotional problems, and family poverty) were carefully controlled. et al, 1996) and the conceptualization of QoL in individuals with IDs (Lee et al, 2020).…”
Section: Respondentsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Access to existing provision has previously been found to depend on socioeconomic and family circumstances. 23 , 25 For example, families of children with Down syndrome—who tend to report a lower incidence of poverty and higher levels of parental education compared to families of children with other neurodevelopmental disabilities 36 , 37 are more likely to report having their support needs met. 38 , 39 We found that in some cases, autism support was accessed by families as a result of parents' professional or social networks.…”
Section: Discussionmentioning
confidence: 99%
“…These results were replicated in subsequent studies [ 72 , 82 ]. A more recent study comparing mothers of children with DS with mothers of children with ID of mixed etiologies reported that the initial group differences in psychological distress and life satisfaction were largely associated with family poverty [ 83 ]. In summary, it emerges that research on parenting stress levels in DS needs to take into account SES when comparing reports from parents of children with DS with parents of children with other genetic conditions and/or other IDs.…”
Section: Discussionmentioning
confidence: 99%